2001
DOI: 10.4049/jimmunol.166.5.3574
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Osteoclast Differentiation Factor Is Induced by Lipopolysaccharide in Mouse Osteoblasts Via Toll-Like Receptors

Abstract: Osteoclast differentiation factor (ODF), a recently identified cytokine of the TNF family, is expressed as a membrane-associated protein in osteoblasts and stromal cells. ODF stimulates the differentiation of osteoclast precursors into osteoclasts in the presence of M-CSF. Here we investigated the effects of LPS on the gene expression of ODF in mouse osteoblasts and an osteoblast cell line and found that LPS increased the ODF mRNA level. A specific inhibitor of extracellular signal-regulated kinase or protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
190
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(210 citation statements)
references
References 50 publications
12
190
2
6
Order By: Relevance
“…In addition, in another experimental system, challenge with purified Aggregatibacter actinomycetemcomitans and Escherichia coli LPS also upregulated RANKL expression through the p38 MAPK pathway, in line with the present findings [33]. However, another study demonstrated that these two LPS induced RANKL expression in murine osteoblasts, mediated by the ERK MAPK pathway [34]. These discrepancies highlight the utilisation of different signalling pathways by different cell 13 types, in response to similar challenges.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, in another experimental system, challenge with purified Aggregatibacter actinomycetemcomitans and Escherichia coli LPS also upregulated RANKL expression through the p38 MAPK pathway, in line with the present findings [33]. However, another study demonstrated that these two LPS induced RANKL expression in murine osteoblasts, mediated by the ERK MAPK pathway [34]. These discrepancies highlight the utilisation of different signalling pathways by different cell 13 types, in response to similar challenges.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, we found that TLR3 was expressed in E1 cells. In support of our findings, it has been reported that TLR3 mRNA was constitutively expressed in primary mouse osteoblasts (26). Our study revealed that poly(I):poly(C) up-regulated TLR3 expression in E1 cells.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that LPS induces RANKL expression by the mechanism independent of PGE 2 production. Kikuchi et al (40) reported that LPS induces RANKL through extracellular signal-regulated kinase (ERK) and PKC. We also confirmed that calcium/ PKC inhibitors, such as BAPTA-AM (an intracellular calcium chelator) and Ro-32-0432 (a PKC inhibitor), and ERK inhibitor PD98059 inhibited LPS-induced RANKL mRNA expression in osteoblasts (K.S., unpublished observation).…”
Section: Discussionmentioning
confidence: 99%